Volumetric tissue reduction in radiofrequency surgery of the tongue base - Stuck, Boris; Köpke, Julian; Hörmann, Karl; Verse, Thomas; Eckert, Andreas; Bran, Gregor M.; Düber, Christoph; Maurer, Joachim T. (Otolaryngology - head and neck surgery, 2005)
OBJECTIVES:, Radiofrequency surgery is a minimally invasive technique for the treatment of the tongue base in sleep-disordered breathing. The aim of this study was to evaluate the changes in upper airway anatomy induced by radiofrequency surgery with MRI., STUDY DESIGN AND SETTING:, 10 patients with sleep-disordered breathing were treated with radiofrequency surgery at tongue base. MRI measurements were performed before and after surgery with the help of a recently published protocol., RESULTS:, The mean total number of energy delivered per patient was 4750 ± 1641 Joule. Relevant changes could be observed neither for tongue volume or dimension nor for retrolingual space., CONCLUSIONS:, Changes in upper airway anatomy could not be demonstrated. The effects of radiofrequency surgery of the tongue base may more likely be a result of changes in upper airway collapsibility., SIGNIFICANCE:, Functional effects of surgical interventions in sleep-disordered breathing should be considered in addition to mechanistic concepts alone.